Pengaruh Capital Adequacy Ratio (CAR) dan Loan to Deposit Ratio (LDR) Terhadap Pertumbuhan Laba pada Bank Konvensional di Indonesia Periode 2019–2023 - Sundari, Annisa Pratiwi; Alfiana, Alfiana; Kodariah, Siti (Indo Publishing, 2026)
This study examines the effect of the Capital Adequacy Ratio (CAR) and Loan to Deposit Ratio (LDR) on profit growth in conventional banks in Indonesia during the 2019–2023 period. The data were processed using EViews 12 through panel data regression, which involved data preparation, descriptive statistical testing, normality testing, classical assumption testing, and model selection procedures using the Chow, Hausman, and Lagrange Multiplier (LM) tests. The results show that the Random Effect Model (REM) is the most appropriate panel regression model for this research.The findings indicate that CAR has a positive and significant effect on profit growth, while LDR has a positive but insignificant effect. Simultaneously, both variables significantly influence profit growth with an R² value of 93.03%, demonstrating strong explanatory power. These results highlight that capital strength plays a crucial role in supporting bank performance, whereas credit distribution effectiveness—represented by LDR—does not significantly drive profit growth during the study period.